Work-Family Conflict, Anger and Verbal Aggression among Married Women with Paid Job: Moderating Role of Perceived Social Support - Dr. Riffat Sadiq [1st Author/Corresponding author]; Ms. Ammarah Saleem [2nd Author]; Ms. Faiza Anwar [3rd Author] (Al-Qanṭara, 2024)
The present study aimed at investigating the relationship of work-family conflict with anger and verbal aggression with moderating role of perceived social support among married women with paid job. Total three hundred (n =300) married women affiliated with various organizations were conveniently recruited from Faisalabad and Lahore. Data were collected administering demographic information form, Work-Family Conflict (Haslam et al., 2015), Multidimensional Scale of Perceived Social Support (Zimet et al., 1988), Anger and Verbal Aggression, Subscales of Aggression Questionnaire (Buss & Perry, 1992) on the selected sample. Statistical analysis revealed majority women experiencing significant anger and verbal aggression. Work-family conflict has significant relationship with anger and verbal aggression and that relation was moderated by perceived social support from family, friends and significant others. The present findings have implications for family and society emphasizing on sufficient provision of social support for married women with paid job not only for the successful resolution of work-family conflict but also for managing their anger and verbal aggression to be functional within work-family spheres